2007
DOI: 10.1111/j.1365-2990.2007.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of osteopontin is increased in vessels with blood–brain barrier impairment

Abstract: These findings indicate that the expression of osteopontin is increased in BBB-damaged vessels in hypertensive SHRSP compared with that in vessels without BBB impairment in WKY rats, suggesting a role for osteopontin in BBB function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…The protein has been extensively studied in multiple sclerosis, where it appears to be involved, through the ␣ 4 ␤ 1 integrin, in the entry of effector T cells in the brain (41), and through CD44 receptor, in the permanence of T cells at the site of inflammation. Recent information has suggested that the levels of OPN in CSF are not disease specific, but can point to involvement of the CNS or damage to the blood-brain barrier (BBB) (44,45). The levels of OPN in the CSF of S2 HAT patients analyzed in the present study were significantly higher than in S1 patients, suggesting an association between CSF OPN and disease progression.…”
Section: Discussionmentioning
confidence: 37%
“…The protein has been extensively studied in multiple sclerosis, where it appears to be involved, through the ␣ 4 ␤ 1 integrin, in the entry of effector T cells in the brain (41), and through CD44 receptor, in the permanence of T cells at the site of inflammation. Recent information has suggested that the levels of OPN in CSF are not disease specific, but can point to involvement of the CNS or damage to the blood-brain barrier (BBB) (44,45). The levels of OPN in the CSF of S2 HAT patients analyzed in the present study were significantly higher than in S1 patients, suggesting an association between CSF OPN and disease progression.…”
Section: Discussionmentioning
confidence: 37%
“…14,15 We then examined differences in gene expression between microdissected hippocampal vessels with BBB impairment in SHRSP and those without the impairment in Wistar Kyoto (WKY) rats using a microarray assay and reported that the expression of osteopontin, a matricellular protein, was increased in BBB-damaged vessels in hypertensive SHRSP compared with that in vessels without BBB impairment in WKY rats. 16 The study also indicated that the immunoreactivity of osteopontin was present in perivascular ED1-positive macrophage/microglial cells and suggested the possibility that osteopontin might act as an inducible modulator of vascular remodeling, which likely restored BBB function in the damaged blood vessels. In addition, we recently reported 17 that the expression of P-glycoprotein, a representative efflux transporter in the brain vessels, was increased in vessels with BBB impairment in the hippocampus of SHRSP.…”
Section: Introductionmentioning
confidence: 76%
“…In addition, the results in the microarray assay also indicated that the expression of transforming growth factor-b receptor II was increased in the hippocampal samples of SHRSP, compared with that in the samples of WKY rats. 16 It is known that transforming growth factor-b enhances MMP-13 expression. 35,36 The increased expression of MMP-13 together with transforming growth factor-b receptor II in the BBB-damaged vessels of SHRSP is compatible with these findings reported earlier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations